A Modular Setup to Run a Large Line of Behavioral Testing in Mice in a Single Space. Issue 1 (8th September 2020) - Manno, Rachel; Witte, John; Papouin, Thomas
Abstract: Elucidating the complex neural mechanisms that underlie cognition is contingent upon our ability to measure behavioral outputs reliably in animal models. While the development of open‐source software has made behavioral science more accessible, behavioral research remains underappreciated and underutilized. One reason is the large real estate necessitated by traditional behavioral setups. Space must be specifically allocated for a controlled testing environment, accommodate the large footprint of mazes used in behavioral research, and allow a contiguous computerized area for data acquisition. Additionally, to achieve the distinct and sometimes incompatible environmental conditions required by different tasks, a suite of testing rooms may be necessary. Because space is a limited resource, this makes behavioral testing impractical for some labs or leads to implementation of suboptimal solutions that compromise the ergonomics of the working space, prevent the adequate control of environmental parameters around the testing setup, and jeopardize experimental reproducibility. Here, we describe a modular, space‐saving, self‐sufficient, functional, customizable, and cost‐efficient setup to allow a large line of behavioral tests in mice within a single, compact room (<8 m 2 ). Because it is modular by design, this setup requires no compromises on ergonomics, environmental control, or complexity of the visual landscape. It is inherently effective at streamlining behavioral experiments by eliminating the need to redefine tracking parameters, and makes swapping between configurations fast (∼1 min) and effortless. Presently, this design allows one to run eight major behavioral tasks, permitting a detailed and comprehensive analysis of mouse behavior within the footprint of a small office. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Constructing the support table Support Protocol 1 : Constructing the open‐field maze Support Protocol 2 : Constructing IR‐permissive inserts for light‐dark assays Support Protocol 3 : Constructing the three‐chamber maze Support Protocol 4 : Constructing the Y maze Support Protocol 5 : Constructing the elevated plus maze Support Protocol 6 : Constructing the Barnes maze Basic Protocol 2 : Setting up the behavior room: flange and pulley systems Basic Protocol 3 : Setting up the behavior room: environmental and storage systems Basic Protocol 4 : Assembling and switching between configurations